Political Connections, Business Groups, and Firm Value in Indonesia: English - Radya, Muhammad Fasha; Suranta, Eddy (Ilomata International Journal of Tax and Accounting, 2025)
This study examines the impact of politically connected board directors on firm value, with business group affiliation serving as a moderating variable, focusing on Indonesian manufacturing firms. Drawing on agency theory and resource dependence theory, the research analyzes 318 observations from 106 listed companies between 2020 and 2022. Tobin’s Q is used as a measure of firm value. The findings reveal that political connections alone do not significantly influence firm value (PCBOD = 0.421, PCBOD2 = 0.106), but their effect becomes positive and significant when moderated by business groups (PCBOD×BG = 0.006, PCBOD2×BG = 0.007). This implies that business group structures, particularly in family-controlled firms, can enhance the strategic value of political ties. The study is limited by its broad classification of political connections, without distinguishing their type or depth. Future research should examine more specific political affiliations and consider political dynamics across sectors.